Scottish Lettering of the 16th century - Harrison, Aidan; Burnett, Charles J (Proceedings of the Society of Antiquaries of Scotland, 2018)
Surviving visual culture from the early modern period that can be described as particularly Scottish in style is scarce. As a result, any evidence of such artistry is of national significance. The purpose of this article is to draw attention to a form of lettering which was used for the display of short inscriptions and initials in Scotland throughout the 16th century. Surviving examples are almost exclusively carved in relief in durable wood and stone. This distinctive letterform is drawn from the transitional styles which briefly appeared at the end of the 15th century as French artists and scribes transferred their allegiance from their traditional ornate Gothic capitals to the bold, simple Roman forms of the Renaissance. While a number of experimental letterforms fleetingly appeared elsewhere across northern Europe, Scottish scholars absorbed these new influences in France and developed them into a distinctive form which persisted in Scotland for over a century. After its first known appearance at the marriage of King James IV to Margaret Tudor in Edinburgh in 1503, the evidence suggests that the use of Scottish Lettering became confined to Aberdeen and the north-east, primarily in pre Reformation ecclesiastical applications. Following the Reformation, it became largely restricted to secular and funerary inscriptions.